A tool for tracking and assessing chronic illness care in prison (ACIC-P). - Wang, Emily A; Aminawung, Jenerius A; Ferguson, Warren; Trestman, Robert; Wagner, Edward H; Bova, Carol (Journal of correctional health care : the official journal of the National Commission on Correctional Health Care, 2014)
Chronic disease care is being transformed in correctional settings, given an aging inmate population, ongoing quality improvement efforts, litigation, and rising costs. The Chronic Care Model, established for chronic disease care in the community, might be a suitable framework to transform chronic disease care in prison, but it has not been systematically adapted for the correctional health care setting. We employed cognitive interviewing to adapt an extant survey used to measure the delivery of chronic illness care in the community, Assessment of Chronic Illness Care, for a prison setting. Results from the cognitive interviews and the modified Assessment of Chronic Illness Care-Prison (ACIC-P) instrument are presented in this article. Future studies will need to test the reliability and psychometric properties of the adapted ACIC-P.
Keywords: Adult; Chronic Disease; Delivery of Health Care; Female; Humans; Middle Aged; Prisons; Quality of Health Care; Reproducibility of Results; Self Care; United States